2016
DOI: 10.5152/balkanmedj.2016.16560
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Radiotherapy in the Treatment of Primary or Recurrent Desmoid Tumors and Long-Term Results

Abstract: Background: Desmoid tumors are uncommon and benign mesenchymal neoplasms. The optimal treatment of patients with desmoid tumors is still controversial. Surgery is the primary treatment for locally invasive or recurrent desmoid tumors. Also, radiotherapy is a treatment option for patients at high risk for local failure such as those with positive margins or recurrent and unresectable tumors. Aims: To report our institutional experience and longterm results of patients with desmoid tumors who received radiothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Collectively, our study echoed previous studies in the largest sample size indicating that SABT was characterized not only by good e cacy but also by low and accepted toxicity in recurrent AF. Ergen et al (29) reported the e cacy and toxicity of radiotherapy for primary or recurrent AF patients with prior irradiation. In the study, the 2-and 5-year LCT rate of radiotherapy (18 patients received solo EBRT, 1 received EBRT combined with brachytherapy and 1 received solo brachytherapy) for AF was 80% and 69% respectively with a median LCT of 33 months.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Collectively, our study echoed previous studies in the largest sample size indicating that SABT was characterized not only by good e cacy but also by low and accepted toxicity in recurrent AF. Ergen et al (29) reported the e cacy and toxicity of radiotherapy for primary or recurrent AF patients with prior irradiation. In the study, the 2-and 5-year LCT rate of radiotherapy (18 patients received solo EBRT, 1 received EBRT combined with brachytherapy and 1 received solo brachytherapy) for AF was 80% and 69% respectively with a median LCT of 33 months.…”
Section: Adverse Eventsmentioning
confidence: 99%